Shale gas development and crime: a review of the literature - Stretesky, Paul B.; Grimmer, Philipp E. S. (The Extractive Industries and Society, 2020)
This systematic review summarizes the relationship between shale gas development and crime. A comprehensive search uncovered 25 shale-crime quantitative studies published between 2005 and 2019. These outputs suggest the study of shale gas development and crime is multidisciplinary, increasing rapidly and mainly carried out in the United States. When considered in aggregate these studies provide clear evidence that shale gas development is likely to increase crime. A majority of studies find that shale gas development increases total crime, violent crime, property crime, social disorganization crimes and violence against women. We conclude by suggesting that these findings should be considered by policymakers and planners when determining whether and how shale development should be allowed.
Gesehen am 16.10.2020